Peculiarities of Ethical and Pedagogical Approach to Realization in Professional Education - Хоружая, Людмила Леонидовна (Pedagogika, 2013)
Nowadays the transdisciplinary approach to assessment of new developments in the modernization of education is actively developing in the modern science. Being the methodological basis for the implementation of this process, ethical and pedagogical approach can fil it with the ethical and moral content and bring valuable substance to the process. In the professional education, ethical and pedagogical approach is viewed as the pedagogical instrument for the systemizing and strengthening of the humanistic approach to training of future professionals. With the help of such approach, it becomes possible to implement the dominant axiological idea of education into the practical work and, ultimately, increase its effectiveness. The realization of the above approach into the process of student‘s education has impact on the strategy and tactic of interaction with students, serves as a benchmark in the process of educational content selection, becomes the condition and method of achieving the new quality of education. Theoretical comprehension of the scientific problem allows to conclude that ethical and pedagogical approach applies both to general- and specific scientific methodological levels. The usage of terms ethical and pedagogical is theoretically justified by interaction of ethical and pedagogical knowledge, which involves the formation of a system of individuals‘ values. The conjunction between of ethical and pedagogical aspects agrees with the primary purpose of pedagogy as a science aimed at studying the personality, giving help in the development of personality, personality’s socialization, formation of moral values and rules of behavior, mastering ethical professional norms. The ethical component of this approach provides direction for pedagogical one and fills it with the moral and ethical content. The components of this approach interact with each other. The article sets basic principles of ethical and pedagogical approach to professional education of professionals working in the system “Human - human”: system-based approach, subjectivity, social and personal development, adherence to cultural values, adherence to the principle of deontology, reflexive and values-based goal-setting. The article also comments on the implementation of ethical and pedagogical approach to modern professional education and its key components (motivational and values-driven, cognitive and technological) Motivational and values-driven component of ethical and pedagogical approach reflects the level of penetration of the ethical one into the sphere of professional values of an individual. Thus, with the help of pedagogy we can ensure that the area of professional activities and competences of a future professional is enriched with moral values. This is achieved through formation of moral values and “benchmarks”. The range of values of a professional who is going to work in the system “Human - human” is defied. Cognitive component is realized in the course of student’s mastering specific system of knowledge, standards and rules which have influence on the formation of student’s subject - subject relations in the profession. Technological component of the realization of ethical and pedagogical approach in the professional education defies the technological aspect of the process. The attention is focused on the dialog-based forms of training, identification and analysis of students’ views and judgments, development of studentocentrism. The material set in the article helps professors and teachers to systemize the educational process in the university and make it ethical and pedagogical. The conclusion was made about the approach being universal and integrated, as well as values-oriented.